A new species of Tanaopsis (Crustacea: Tanaidacea) from Japan, with remarks on the functions of serial ridges and grooves on the appendages - Kakui, Keiichi; Shimada, Daisuke (Zootaxa, 2017)
We describe Tanaopsis japonica sp. nov. from intertidal and nearshore habitats around Hokkaido Island, northern Japan. This species closely resembles T. chotkarakde Bird & Bamber, 2000 and T. rawhitia Bird, 2011 in having the uropod with the endopod biarticulate and the exopod uniarticulate, but differs from them in the following characters: pereonite 4 as long as pereonite 5; mandibles lacking the molar; the number of simple setae on the antenna, propodal palm, and dactylus of pereopods 1–3; the number of spiniform setae on the cutting surface of the chelipedal dactylus; and the number of setae on the pleopods. We also determined a nearly complete nucleotide sequence for the 18S rRNA gene in T. japonica. In both sexes, Tanaopsis japonica sp. nov. bears serial ridges and grooves on the chela, antennule, and antenna. Parallel, fringed hatch marks on the chelipedal dactylus may function in stridulation. A series of denticulate ridges on the dorsal surface of antennal article 2 faces the ventral side of article 1 of the antennule, where there is a ventral series of slight grooves. Although the ranges of motion of the antennule and antenna were unclear, the ridges and grooves on the antenna and antennule may also function in producing sound. Two outer series of ridges on the chela, together with an outer furrow on the chela, may function in digging, by allowing bottom-sediments to be efficiently pushed aside.